Autoevaluación de prácticas inclusivas docentes en atención a la población con aptitudes sobresalientes - Márquez Cabellos, Norma Guadalupe; Andrade Sánchez, Adriana Isabel; García Cedillo, Ismael (Universidad de Costa Rica, 2021)
Inclusive practices in the school context involve the use of a variety of strategies by teachers to ensure the learning and participation of all students. The objective of this research was to analyze the self-evaluation of inclusive practices of teachers who serve adolescents with gifted abilities from a secondary school with a semi-boarding modality in the state of Colima, Mexico. A quantitative, cross-sectional study was designed, with a descriptive scope, where 34 teachers who worked in the 2019-2020 school year participated. Data were collected through the Guide for the Evaluation of Inclusive Practices in the Regular Classroom –GEPIA- Self-Report Format, the Self-Efficacy Scale to Implement Inclusive Practices and the Questionnaire on Strategies to Strengthen Learning. For the reliability of the instruments, Cronbach's Alpha was calculated and descriptive and inferential statistics techniques were applied for data treatment, as well as the Mann-Whitney U. The results indicate that teachers self-evaluate with inclusive good practices, by implementing diversified strategies in methodology and evaluation, as well as by promoting collaborative work with the school community and linking with parents. However, teachers mention that they need training, updating and training on issues related to inclusive education and attention to gifted skills. They also indicate that they require more resources to promote learning among their students. It is concluded that inclusive practices positively value school diversity, lead to the mobilization of pedagogical actions for the achievement of quality in learning and the satisfaction of educational needs of the gifted population.